The Autonomous Learners’ Language Learning Strategies at Senior High Schools in Coastal Areas of Riau Province - Indonesia - Ras, Fakhri (International Journal of Educational Best Practices, 2017)
This study focuses on examining the use of Language Learning Strategies (LLS) by autonomous learners at senior high schools in relation to the type of school and academic factors in Dumai, Bengkalis, and Selat Panjang (coastal areas). The study also concentrates on the preferred by ways operated by the selected respondents to master general English, four language skills, vocabulary, and structure.  The target groups of the research are autonomous learners ( more or less 3000 students) from state senior high schools in three different small towns. Due to the homogenous characters of the target groups; academic achievement, age, and learning motivation, the sample is taken randomly as big as 10% out of the population. To collect the needed data quantitatively, the strategy inventory for language learning (SILL) (Oxford 1990) is applied, and for the qualitative data, an interview is conducted to 60 selected learners out of the sample. To analyze the quantitative data, descriptive and inferential statistics are used and for the qualitative data, listing the preferred ways are made accordingly. The findings reveal that the various LLS are used based on academic and types of school backgrounds. The social strategy is the highest use of LLS (402) among other strategies (memory, cognition, compensation, metacognition, and affection). The qualitative findings exist in the body of this article (table 6 – through table 8). The suggestion is that LLS would be better to be well instructed and discussed in the classroom.